Perbandingan Hasil Belajar Mata Kuliah Ushul Fiqh Pada Mahasiswa Ahwal as-Syakhshiyyah dan Muamalah Angkatan 2014 Ditinjau dari Latar Belakang Pendidikan - Syaiful Ilmi (The Pontianak State Institute of Islamic Studies, 2016)
This research discusses the improvement of learning achievement among students of the faculty of Sharia particularly the departments of Ahwal as-shakhsiyyah and Muamalah. This is because both are religion-based and newly-opened departments in the Sharia Faculty. Therefore, the researcher is interested in doing research on learning outcomes of the usul fiqh course viewed from the educational background of the students in both majors before entering college. Preliminary observations show that learning outcomes in usul fiqh among students of Ahwal as-Shakhsiyyah and Muamalah class of 2014 with a background of public schools and religious schools tend to be similar. In fact, students of religious educational background should have better outcomes than their peers with in public school educational background. This research focuses on the following problems: 1) the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from religious schools; 2) the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from public schools; 3) comparison between the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from religious schools and those who from Public schools. This research uses a quantitative approach that is descriptive analytical. Techniques used in data collection are assessment techniques and techniques of documentary studies. The technique of data analysis uses descriptive analysis and t-test using SPSS calculations. The research found that: the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from religious schools were good. Second, the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from public schools were quite good, and third there was indifferent achievement the learning outcomes in the course of Usul Fiqh among Students of Ahwal as-shakhsiyyah and Muamalah 2014 who graduated from religious schools and those who from Public schools.